2010
DOI: 10.1111/j.1440-1738.2010.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Detailed measurements of thickness and grain size of a widespread onshore tsunami deposit in Phang‐nga Province, southwestern Thailand

Abstract: Measurements of thickness and grain size along flow-parallel transects across onshore deposits of the 2004 Indian Ocean tsunami revealed macroscopic horizontal variations and provided new insights into tsunami sedimentation. The tsunami caused severe erosion of beaches, river mouths, and the shallow seafloor along the coast of southwestern Thailand and supplied sufficient sediment to deposit a kilometer-wide blanket of sand on the land surface. The tsunami deposits generally fine landward with some fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
3
46
0
1
Order By: Relevance
“…For instance, the thickness of the tsunami deposits, in the range of a few mm to approximately 40 cm and being approximately 10 cm on average, is very similar to those reported from the adjacent areas (Hori et al, 2007;Fujino et al, 2010), as well as from the other areas affected by the IOT (e.g., Moore et al, 2006) or other tsunamis (e.g., Gelfenbaum and Jaffe, 2003). This study found common features such as normally graded and massive layers.…”
Section: Iot Deposits Characteristicssupporting
confidence: 69%
See 2 more Smart Citations
“…For instance, the thickness of the tsunami deposits, in the range of a few mm to approximately 40 cm and being approximately 10 cm on average, is very similar to those reported from the adjacent areas (Hori et al, 2007;Fujino et al, 2010), as well as from the other areas affected by the IOT (e.g., Moore et al, 2006) or other tsunamis (e.g., Gelfenbaum and Jaffe, 2003). This study found common features such as normally graded and massive layers.…”
Section: Iot Deposits Characteristicssupporting
confidence: 69%
“…During the last 15 years, much effort has been devoted to documenting the various recent tsunami deposits (Nishimura and Miyaji, 1995;Sato et al, 1995;Shi et al, 1995;Dawson et al, 1996;Minoura et al, 1997;Bourgeois et al, 1999;Gelfenbaum and Jaffe, 2003;Nanayama and Shigeno, 2006;Higman and Bourgeois, 2008;Goto et al, 2011;Moore et al, 2011). The majority of these works focused on documentation of the 2004 Indian Ocean Tsunami (IOT) depositional effects along the coasts of Sumatra (Moore et al, 2006;Razzhigaeva et al, 2006;Richmond et al, 2006;Paris et al, 2007Paris et al, , 2009, Thailand (Hori et al, 2007;Kelletat et al, 2007;Choowong et al, 2008a, b;Matsumoto et al, 2008;Sawai et al, 2009;Fujino et al, 2010;Naruse et al, 2010), Sri Lanka (Morton et al, 2008), India (Bahlburg and Weiss, 2007;Srinivasalu et al, 2007) and Maldives (Kench et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Thailand, tsunami-related erosion and sedimentation were reported both onshore (e.g., Szczuciński et al, 2006;Choowong et al, 2007Choowong et al, , 2009Hawkes et al, 2007;Hori et al, 2007;Kelletat et al, 2007;Umitsu et al, 2007;Fagherazzi and Du, 2008;Fujino et al, 2008Fujino et al, , 2010Goto et al, 2008;Matsumoto et al, 2008;Sawai et al, 2009;Yawsangratt et al, 2009; and offshore (Chavanich et al, 2005;Feldens et al, 2009;Sugawara et al, 2009). Thicknesses of the onshore tsunami deposits were as great as 60 cm (Szczuciński, in press).…”
Section: Impact Of the 2004 Indian Ocean Tsunami At Thailandmentioning
confidence: 99%
“…For example, local variation of the thickness of the tsunami deposits, which is observed between the pits of few meters in horizontal scale, caused by undulation of the topography, is an important factor to interpret the preservation potential of the deposits. In fact, the tsunami deposit thickness is known to be highly variable with several to several tens of centimeters' thickness, depending on local undulation (Hori et al, 2007;Fujino et al, 2010;. To study the preservation potential, a pit in the same place as that examined before should be avoided because the deposits were disturbed during prior digging and covered with other soil (Szczuciński, in press), which in turn suggests that it is not possible to study exactly the same pits, although pits in very close proximity should be studied to compare the preservation potential and thickness variation.…”
Section: Introductionmentioning
confidence: 99%